Intestinal knot in acute Meckel’s diverticulitis - Don Evana Ezrien; Mohd Firdaus Mohd Hayati; Nik Amin Sahid Nik Lah; Andee Dzulkarnaen Zakaria (BMJ Publishing Group, 2019)
A 47-year-old man, with no past surgical history presented to the emergency department with colicky abdominal pain since 2 days prior to the admission. It was associated with abdominal distension, vomiting and no bowel output. The pain became worsened which resulted in his immediate hospital visit. On examination, the abdomen was peritonitic. The blood investigations showed marked leucocytosis. There were signs of small blood obstruction on abdominal radiograph but no free gas on erect chest radiograph. He was immediately rushed to the emergency operation theatre and exploratory laparotomy was performed. Upon entry, there was gangrenous small bowel caused by an ileo-ileal knot with Meckel’s diverticulitis, which was adjacent to the caecum. We had to proceed with limited right hemicolectomy and functional end-to-end anastomosis using linear stapler. The recovery process was uneventful. Patient was discharged home after a week. On follow-up at 3 months, he was well with no complications. The histopathological examination was consistent with ischaemic bowel.